Pengaplikasian Metode Edge pada Perancangan Hotel Resort Pulau Larea-Rea di Kabupaten Sinjai - Nurlinda, Nurlinda; AS, Zulkarnain; Juddah, Safruddin (TIMPALAJA : Architecture Student Journals, 2025)
Travel is very important to reduce stress because traveling is now one of the most popular things among daily activities. South Sulawesi is one of the provinces in Indonesia whose tourism sector is growing rapidly. Sembilan Island, which consists of nine small islands or islets, is located in Sinjai Regency and is one of the places to visit in South Sulawesi. This island is only 12 miles from the center of Sinjai City. In the process of designing a resort hotel, it is important to understand the design approach needed and the design foundations needed. The research methods used are data collection methods and data analysis methods. Data collection methods consist of field surveys, literature research, and precedent research, while data analysis methods are processing or analyzing data that has been collected to help the next planning process. These two methods will help determine the formulation of the problem and how the principles of green building design are implemented through the EDGE method. The results of this study aim to apply design with site analysis that meets so as to produce building design output that can adapt to the surrounding environment. From the research results, it can also be concluded that in this research process, it will be carried out as a design method for the design of the Larea-rea Island resort hotel in Sinjai Regency with the theme of applying the EDGE method, which applies the principle of green building to create sustainable and environmentally friendly buildings using renewable energy, namely solar photovoltaic with a roof area of ​​1,032.79 m² and a power of 150.99 kWp; the second is material efficiency, namely the use of light steel and wood materials on the roof of the building; and the third is water saving, namely grey water wastewater treatment.